Partisipasi Masyarakat dalam Musyawarah Perencanaan Pembangunan Desa - Hadawiya, Rafi’atul; Muda, Indra; Batubara, Beby Masitho (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
The purpose of this study was to how community participation and influencing factors in the village musrenbang in Karang Gading Village, Secanggang District, Langkat Regency. The problem is focused on the implementation of the village musrenbang. To approach this problem the theoretical reference from Cohen and Uphoff is used. Data collected through observation, interviews, documentation, and analyzed using descriptive qualitative methods. The results of the study show that community participation in the village musrenbang is still low with the presence of the community who have not fully attended the invitation to the implementation it is based on several reasons, one of which is the community's distrust of the village government to provide decision results and community participation in the form of making proposals to be prioritized programs and providing suggestions/criticisms on the programs offered is also still low based on the level of community attendance. as for the factors that influence community participation are internal factors consisting of low public awareness, education level, and employment and income. and external factors consisting of the role of the village government such as the lack of socialization and the required facilities and infrastructure.